“Maria Anto, a phenomen in the Cortina Gallery” – Dino Buzzati’s unique discovery in Warsaw - Reinhard Chlanda, Małgorzata (Ars inspiratio: Studies dedicated to Professor Eleonora Jedlińska, 2024)
Maria Anto’s most spectacular success in Italy came in the 1970s. Anto’s “discoverer” for Italy was Dino Buzzati, who considered the Polish artist one of the most original personalities in the field of contemporary fantasy art. He became fascinated with her paintings during a visit to Warsaw in 1969. The famous writer and painter undoubtedly shared a related type of poetic imagination, an atmosphere of imagery. Thanks to the writer’s recommendation, in 1971, a large individual exhibition of Anto’s works was held at the renowned Galeria Cortina in Milan. This event had a great resonance in the artistic and intellectual community of Milan. The famous critic and poet Roberto Sanesi devoted an extensive essay to the artist in the catalog. In the press, among others: “Corriere della Sera” commented on the exhibition: Dino Buzzati, Raffaele Carrieri, Emillio Radius. Critics tried to define the phenomenon of Anto’s work, looking for the specificity and cultural references of her painting. Following her first success in Milan, the artist exhibited in Italy several more times. Over the course of fifteen years, until 1996, she showed works in galleries in Milan, Verona, Trieste, Parma, Vicenza and Rome.